Highlighting Customer Attitudes: A Case Where the Influencer's Credibility and Digital Persuasive Content Are Not Lucrative - Maghfiroh, Lailatul; Anjaningrum, Widiya Dewi; Reyes, Alma Pia G.; Fernandez, Khriz N. (Jurnal Aplikasi Manajemen, 2025)
Viva Cosmetics, one of the oldest makeup brands in Indonesia, is facing stiff competition from local and international brands, raising challenges to encourage consumers' intention to buy their products and potentially to lose their brand prestige. Hence, building positive feelings in customers is essential to drive them to buy. This study examines how influencer credibility and persuasive content affect people's desire to buy, with customer attitudes as the mediating factor. The population comprises all customers of Viva Cosmetics in Indonesia. We collected data via an online questionnaire using a quantitative approach, selecting 290 respondents through accidental sampling. The study employed PLS-SEM and analysis involving SmartPLS 4.1.0.8 to evaluate the research model and test proposed hypotheses. The importance of influencers and persuasive content lies in their power to improve customers' positive attitudes, affecting their plans to buy, making the customer's mindset a full mediator. This study adds to the theory of planned behavior by looking at local cosmetic brands and showing how customer attitude connects outside factors with buying decisions. Influencers with strong credibility and engaging content can enhance customers' emotions, a crucial factor in predicting their behavior when purchasing cosmetics. Consequently, the Viva brand must carefully choose trustworthy influencers, provide convincing content, and closely monitor consumer sentiment.